Avaliação energética do ciclo de refrigeração por absorção utilizando biogás de aterros sanitários e gás natural - Moreira, Heloísa Beatriz Cordeiro [UNESP] (2007)
Recently, because of the energy crisis, the environmental and economical problems, the politics of incentive of the natural gas and the growing importance of cogeration applications, a growing interest has been obseved toward application of absorption cycles, due to the possibility of energy use, for useful ends, of the residual heat of different processes. Coolers (chillers) of absorption have been used widely in industries of air conditioning, partly because they can be operated by hot water, vapor, natural gas, solar energy, biomass, among other, instead of electricity, since approximately 15% of all the electricity produced is globally used for refrigeration and air conditioning according to the International Institute of Refrigeration in Paris (IIF/IIR). Thir work has as the main objective to evaluate a cycle of refrigeration for absorption with solution of lithium bromide-water using biogas of sanitary landfill and mixtures of this with natural gas. By obtaining the energy potential of the biogas of sanitary landfill, natural gas and their mixtures, using the software Combust, it was simulated with the software EES (Engineering Equation Solver), a cycle of refrigeration for absorption with a refrigerating capacity in the range between 18 and 70 kW, which are actual data of equipment of refrigeration for commercial absorption. The analyses of the results showed that the energy viability of the system using in the generator biogas, natural gas and their mixtures when compared with equipments that use traditional fuels (GN, diesel oil, among other), for operation of equipments of refrigeration (chiller) commercial with capacity of refrigeration of 12900 kcal/h and temperature of the water in the...